Seasonal and Solar Cycle Dependency of Relationship Between Equatorial Plasma Bubbles and Rayleigh‐Taylor Instability Growth Rate - L. F. R. Vital; H. Takahashi; D. Barros; C. S. Carmo; A. J. Carrasco; C. M. Wrasse; C. A. O. B. Figueiredo (Space Weather)
Abstract The relationship between the post‐sunset equatorial Plasma Bubbles (EPBs) and the Rayleigh‐Taylor instability growth rates γRT was studied by means of the occurrence probabilities. EPB observations were obtained through the Rate of Total Electron Content Index (ROTI) measured by ground‐based Global Navigation Satellite System (GNSS) receivers in the South American equatorial region. Data from the period 2013 to 2022 were utilized. The γRT calculations were based on F‐layer vertical drift Vp measurements obtained from the São Luís ionosonde (2.33°S, 44.2°W, dip angle: −0.5°), the International Reference Ionosphere model (IRI‐2016), Horizontal Wind Model (HWM‐14), and Spectrometer Incoherent Scatter Model‐2,000 (NRLMSISE‐00). The EPB occurrence probability increased from 0% to 100% as γRT increased from 0 to 2.2×10−3s−1. Additionally, the occurrence probability exhibited seasonal variations, with a gradual increase during the equinox months, minimal occurrence during the June solstice, and a sudden increase during the December solstice. We found that the occurrence probability varied with day‐to‐day, season and solar activity for the same γRT.